2013
DOI: 10.1364/oe.21.021714
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of three-dimensional metamaterial objects and validation by a fast surface-integral equation solver

Abstract: A homogenization model is applied to describe the wave interaction with finite three-dimensional metamaterial objects composed of periodic arrays of magnetodielectric spheres and is validated with full-wave numerical simulations. The homogenization is based on a dipolar model of the inclusions, which is shown to hold even in the case of densely packed arrays once weak forms of spatial dispersion and the full dynamic array coupling are taken into account. The numerical simulations are based on a fast surface-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Taking advantage of LSM in reconstructing both two-dimensional (2D) and 3D images from scattered field data, we present a recently developed novel type spectrally-encoded LSM method using metamaterial leaky wave antennas (MTM-LWAs) to decrease the intricacy of the system and computation costs. In recent years, several MTM platforms have demonstrated exotic electromagnetic (EM) properties [19][20][21][22][23][24][25][26][27][28]. In particular, it is well known that MTM-LWAs exhibit backfire-to-endfire frequency scanning characteristics, and thus can be utilized to cover a wide field of view (FOV) for detecting unknown targets over the operating frequency band [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of LSM in reconstructing both two-dimensional (2D) and 3D images from scattered field data, we present a recently developed novel type spectrally-encoded LSM method using metamaterial leaky wave antennas (MTM-LWAs) to decrease the intricacy of the system and computation costs. In recent years, several MTM platforms have demonstrated exotic electromagnetic (EM) properties [19][20][21][22][23][24][25][26][27][28]. In particular, it is well known that MTM-LWAs exhibit backfire-to-endfire frequency scanning characteristics, and thus can be utilized to cover a wide field of view (FOV) for detecting unknown targets over the operating frequency band [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…at the same frequency) right-handed modes (RHM) and left-handed modes (LHM) of transverse-polarization. This is to contrast with the 3D arrays in [18,19] where the lefthandedness and right-handedness are mutually exclusive. The LHM are supported by the structure even if the chain's particles possess positive polarizabilities and no Bi-isotropy; the needed structural Bi-isotropy is provided by the propagator instead of the particle's local properties.…”
Section: Introductionmentioning
confidence: 93%
“…3D arrays of scalar magneto-electric particles were studied in [17], where the full inter-particle electric and magnetic coupling has been taken into account and the effect of array packaging on the electromagnetic modes has been studied. Such 3D arrays were also studied in [18,19] in the context of homogenization techniques, and it has been shown that the homogenized material may possess negative index properties even if the microscale inclusions are made of conventional material (e.g. spherical particles made of material with positive scalar ǫ and µ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when it consists of an ensemble of particles that form an artificial electromagnetic material, both the particle size and the separation between particles must be much smaller than the operational wavelength in the medium. In fact, it has been recognized that nonlocal effects appear as the particle size and the interparticle distances increase [27][28][29][30][31][32][33]. The study of the force density in the presence of larger particles and the associated complex nonlocal effects is left for future efforts.…”
Section: Force-density Formulationsmentioning
confidence: 99%